The Effect of Blanching, Extraction Methods, and Solvent on Antioxidant Activity, Total Phenols, Flavonoids, and Tannins in Zingiber zerumbet L. Rhizome - Sari, Kartika; Rahmadi, Anton; Rohmah, Miftakhur; Susanti, Vallentina Wahyu Febry; Yunita, Syerly; Maisyaroh, Siti; Saragih, Bernatal (Trends in Sciences, 2025)
Zingiber zerumbet L. has long been used as one of the most popular herbal remedies for treating a wide range of common ailments. This research aimed to evaluate the total levels of tannins, phenols, flavonoids, and antioxidant activity in Z. zerumbet rhizome extract, obtained from 9 - 12 month rhizomes, extract after undergoing a blanching process with 0.05 % citric acid, followed by different extraction methods and solvents. Antioxidant and bioactive component tests were analyzed using 2-way ANOVA, while a t-test was employed to compare the effects of ethanol and distilled water as solvents, assessing their statistical significance. Pearson’s test was used to analyze correlations between variables. A strong positive correlation was observed between total phenol, tannin, and flavonoid content, while IC₅₀ values for DPPH and ABTS assays negatively correlated with bioactive compounds. Blanching Z. zerumbet rhizomes with citric acid, combined with ethanol as the solvent, 24-h maceration, and 30-min sonication resulted in optimal antioxidant capacity and bioactive compound extraction. Blanching with 0.05 % citric acid, followed by extraction using ethanol, 24-h maceration, and 30-min sonication, was identified as the most effective method for maximizing the antioxidant potential of Z. zerumbet. Blanching was found to affect the morphology and solubility of the powdered samples. The FTIR spectra of the powder and extract samples of Z. zerumbet reveal a broad stretching vibration of the O–H bond, along with other detected bonds such as CH₂, C=C, and C–N. The extract sample displays new absorption bands, suggesting the successful extraction of additional compounds during the treatment process. This study underscores the importance of proper extraction methods and pretreatment in maximizing the therapeutic potential of Z. zerumbet as a natural antioxidant source. HIGHLIGHTS Blanching with 0.05 % citric acid enhanced antioxidant and bioactive yield. Ethanol extraction with 24 h maceration and 30 min sonication was optimal. Phenol, tannin, and flavonoid content strongly correlated with antioxidant activity. FTIR analysis confirmed successful extraction of additional functional compounds. XRD and SEM analysis confirmed structural and morphological changes in samples. GRAPHICAL ABSTRACT